Chronic hepatitis C therapy: a rare complication revisited. (26th July 2013) - Yaseen Alsabbagh, Mohammed Eyad; Eisa, Naseem; Alraiyes, Abdul Hamid; Alraies, M Chadi
Abstract : The combined regimen of peg-interferon α2a plus ribavirin along with protease inhibitors (boceprevir or telaprevir) is considered as a very portent and effective therapy for hepatitis C infections. However, this combined therapy has been associated with a side effect that can make the course of the disease more complicated. In this case, a 50-year-old man developed insulin-dependent diabetes soon after initiating triple hepatitis C therapy. The treatment had to be stopped and the course of his hepatitis C infection has been challenged with this rare side effect.